BREAKFAST HABITS, ALLOWANCE, AND NUTRITIONAL STATUS IN RELATION TO MENSTRUAL IRREGULARITIES AMONG HIGH SCHOOL STUDENTS AT SMAN 1 NGAMPRAH - Putri, Intan Rahmadina; Prameswari, Fajria Saliha Puspita; Fitrianingsih, Asti Dewi Rahayu; Astuti, Widya (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Menstrual cycle disorders are a prevalent health issue among adolescent girls and may be influenced by lifestyle factors and nutritional status. This study aimed to examine the association between allowance, breakfast habits, energy adequacy, protein adequacy, fat adequacy, and nutritional status with menstrual cycle disorders among female students at SMAN 1 Ngamprah. A cross-sectional analytical survey was conducted involving 90 students selected through proportional random sampling. Data were collected using questionnaires, 2×24-hour dietary recalls, and anthropometric measurements. The study found a higher prevalence of menstrual cycle disorders among students with above-average allowances, regular breakfast habits, and insufficient intake of energy, protein, and fat. These disorders were also more common in students experiencing both undernutrition and overnutrition. The study concludes that economic factors and nutritional intake are significantly associated with menstrual cycle regularity. Educational interventions promoting balanced diets and effective financial management are recommended as prevention strategies for menstrual cycle disorders among adolescents.